2013
DOI: 10.5863/1551-6776-18.2.88
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Asthma Exacerbation in Children: A Stepwise Approach for Escalating Therapy in a Pediatric Intensive Care Unit

Abstract: OBJECTIVES An increasing prevalence of pediatric asthma has led to increasing burdens of critical illness in children with severe acute asthma exacerbations, often leading to respiratory distress, progressive hypoxia, and respiratory failure. We review the definitions, epidemiology, pathophysiology, and clinical manifestations of severe acute asthma, with a view to developing an evidence-based, stepwise approach for escalating therapy in these patients. METHODS Subject headings related to asthma, status asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
90
0
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(105 citation statements)
references
References 165 publications
2
90
0
13
Order By: Relevance
“…"Status astmaticus"; yirmi dört saatten uzun süren, ağır, hayatı tehdit eden astım ataklarının genel terminolojisi olarak kullanılmıştır, hızlı etkili beta agonistlere cevapsız, yoğun mukus artışı saptanan, hızlı veya yavaş başlayabilen ataklardır (25)(26)(27) %40'dan fazla PEF variabilitesi olması, Tip 2; önce-sinde, tetikleyen bulunmaması ve normal solunum fonksiyonları olmasına rağmen üç saat içinde gelişen ani ağır atak ile karakterizedir (28).…”
Section: öZel Terminolojili Ataklarunclassified
See 1 more Smart Citation
“…"Status astmaticus"; yirmi dört saatten uzun süren, ağır, hayatı tehdit eden astım ataklarının genel terminolojisi olarak kullanılmıştır, hızlı etkili beta agonistlere cevapsız, yoğun mukus artışı saptanan, hızlı veya yavaş başlayabilen ataklardır (25)(26)(27) %40'dan fazla PEF variabilitesi olması, Tip 2; önce-sinde, tetikleyen bulunmaması ve normal solunum fonksiyonları olmasına rağmen üç saat içinde gelişen ani ağır atak ile karakterizedir (28).…”
Section: öZel Terminolojili Ataklarunclassified
“…Bunların erişkinlerde %13'ünün hafif, %22'sinin orta ve %6'sının ağır astım olguları olduğu gözlenirken, çocuklarda %23'ü hafif, %41'i orta ve % 36'sı ağır olgu olarak bildirilmiştir (25,30).…”
Section: öZel Terminolojili Ataklarunclassified
“…[1][2][3] Bronchodilator and systemic cortico-steroid therapies are the mainstays of emergency department management of asthma exacerbations. Despite appropriate emergency department treatment, up to 27% of these patients require admission, making asthma the most common reason for pediatric hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Despite appropriate emergency department treatment, up to 27% of these patients require admission, making asthma the most common reason for pediatric hospitalization. 3 Status asthmaticus represents an important subset of pediatric asthma exacerbations, with nearly 500,000 patients requiring admission to the pediatric ICU each year. 3 An analysis of our institution's emergency department asthma management revealed that adherence to evidencebased asthma guidelines was suboptimal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation